Active calcium responses recorded optically from nerve terminals of the frog neurohypophysis (The Rockefeller University Press, 1985)
Voltage-sensitive dyes were used to record by optical means membrane potential changes from nerve terminals in the isolated frog neurohypophysis. Following the block of voltage-sensitive Na+ channels by tetrodotoxin (TTX) and K+ channels by tetraethylammonium (TEA), direct electric field stimulation of the nerve terminals still evoked large active responses. These responses were reversibly blocked by the addition of 0.5 mM CdCl2. At both normal and low [Na+]o, the regenerative response appeared to increase with increasing [Ca++]o (0.1- 10 mM). There was a marked decrease in the size of the response, as well as in its rate of rise, at low [Ca++]o (0.2 mM) when [Na+]o was reduced from 120 to 8 mM (replaced by sucrose), but little if any effect of this reduction of [Na+]o at normal [Ca++]o. In normal [Ca++]o, these local responses most probably arise from an inward Ca++ current associated with hormone release from these nerve terminals. At low [Ca++]o, Na+ appears to contribute to the TTX-insensitive inward current.